Ciclo-Ruta Turística para las Parroquias de Chuquiribamba, Gualel y El Cisne del Cantón Loja, Provincia de Loja - Benítez León, Katty Alejandra (2018)
The Canton Loja has six urban parishes and thirteen rural parishes, of which the parishes of the northwestern part stand out, since you can enjoy the warmth of its people, the typical dishes, the beautiful landscapes, culture and charm that has this sector. This work highlights the cultural and natural wealth of the parishes of Chuquiribamba, Gualel and El Cisne; and promotes a new alternative of adventure tourism, in which the use of the bicycle as a sustainable means of transport is fundamental. This research allowed the use of adequate techniques and methods to structure the project; the following objectives were raised; as a general objective: To elaborate the cycle-tourist route for the parishes Chuquiribamba, Gualel and El Cisne of the Cantón Loja, Province of Loja, for the fulfillment of the same three specific objectives were raised; the first: Carry out the tourist diagnosis of the Parrish Chuquiribamba, Gualel and El Cisne of the Cantón Loja, Province of Loja; in which the analytical method was used; the matrix of Carla Ricaurte, the methodology of the Ministry of Tourism (MINTUR) was used as a basis to inventory and prioritize the tourist attractions, and interviews were conducted with the main authorities of the parishes whose results served to carry out the analysis of the strengths, opportunities, weaknesses and threats (SWOT); the second: Design the tourist cycle route that integrates the Chuquiribamba, Gualel and El Cisne of the Cantón Loja parishes, Loja Province, the same that was carried out through the field study, inductive and deductive method, instruments such as the GPS to determine distances, coordinates, travel time, then the design of maps was done using the Qgis program; In addition, the Tourist Signaling Manual of MINTUR was used as a guide; and third: Socialize the results of the research work to those involved in the tourism activity; for the Chuquiribamba, Gualel and El Cisne of the Cantón Loja parishes, Loja Province, the rapid analysis and participatory planning method (MARPP) 5 was used, for which a participatory workshop was held, in order to publicize the contribution that would generate the implementation of the proposal. It is determined that the cycle route is a contribution for the tourist development of the parishes, since through this product the tourist attractions will be promoted; In addition, this work aims to offer visitors new leisure and recreation alternatives. Finally, the Autonomous Decentralized Parochial Government of Chuquiribamaba, Gualel and El Cisne is recommended to work together with the Autonomous Government of the Loja Canton to improve the access roads to the parishes, and with the Ministry of Tourism to involve the inhabitants in the activity; incentivizing them through training and entrepreneurship plans in tourism businesses.